IMPLEMENTATION OF TPACK IN ARABIC FOREIGN LANGUAGE LEARNING FOR LISTENING SKILLS - Presti Multi; Anwar Sanusi; Salman Jufri (Universitas Islam Negeri Palopo, 2026)
This study is motivated by the low level of students’ listening skills (maharah istimā‘) in Arabic language learning, despite the initial use of technology in the instructional process. The study aims to describe the implementation of the Technological Pedagogical Content Knowledge (TPACK) model in teaching listening skills and to identify the challenges encountered in its application. This research employs a qualitative approach with a descriptive design. The research subjects are eleventh-grade students of Madrasah Aliyah Laboratory, Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the TPACK model has not been optimal. The use of technology is limited to the implementation stage, primarily through Arabic-language video as a supporting medium for learning, and has not been systematically integrated into the planning and evaluation stages. Furthermore, the use of technology is not consistently applied in every learning session. The challenges identified include differences in students’ basic abilities and levels of focus, as well as limitations in learning facilities, particularly audio equipment. Therefore, the implementation of TPACK in teaching listening skills requires further development to achieve a more effective integration of technology, pedagogy, and content.